Community health literacy outcome measurement practices: A scoping review of recent interventions. Issue 5 (8th September 2022) - Sawyers, Luke; Anderson, Claire; Aslani, Parisa; Duncan, Gregory; Janjua, Sobia S.; Toh, Li Shean
Abstract: Introduction: Evidence suggests that, while a preference for functional Health Literacy (HL) outcome measurement exists, researchers are converging towards more all‐encompassing instruments. While this claim is present in the HL field, minimal research has comprehensively explored the state of community HL measurement practices at the direct and proxy level. The almost exclusive focus on direct, as opposed to proxy, community HL measurement indicates a review of progress is needed. Objective: To identify HL outcome measurement practices for community HL interventions at the direct and proxy level of measurement. Search Strategy: Medline, PsycINFO, Web of Science, ERIC, Embase, Scopus, CINAHL, ProQuest Dissertations and Theses, Google Scholar and targeted websites were searched. Inclusion Criteria: Studies were sampled from the general population, included HL as an outcome of interest, involved an intervention aiming to improve HL, were English‐text publications and were published ≥2010. Data Extraction and Synthesis: Study author(s) and publication years, sample characteristics, intervention profiles and direct and proxy instrument and outcome measurement information were extracted. Full‐text review retrieved 25 eligible studies. Main Results: In total, 21 unique direct and 38 unique proxy instruments were extracted. The majority of interventions assessed functional compared to communicative, critical, and other HL domains, with objective instruments more frequently used than subjective or combined objective‐subjective types, though more unique subjective HL instruments were extracted overall. The Test of Functional HL in Adults was the most popular instrument, and perceived health, knowledge, behaviors and health intentions were the most frequent proxy outcome measures, with only the Healthy Lifestyle Behavior Scale‐II and Patient Activation Measure used across multiple interventions. Discussion and Conclusions: Direct HL outcome practices endured a unidimensional profile, despite previous suggestions of a convergence towards holistic instruments. This review provides the first overview of proxy HL measurement across community HL interventions, identifying substantial variation in proxy outcome practices. Patient or Public Contribution: A University‐based senior librarian contributed to the development of the search strategy, and reviewed iterations of the strategy until refinement was complete. No further public or patient contribution was made given the review‐based nature of the research.